2010
DOI: 10.1523/jneurosci.2676-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction between Tropomyosin-Related Kinase B Receptors and Presynaptic Muscarinic Receptors Modulates Transmitter Release in Adult Rodent Motor Nerve Terminals

Abstract: The neurotrophin brain-derived neurotrophic factor (BDNF), neurotrophin-4 (NT-4) and the receptors tropomyosin-related kinase B (trkB) and p75NTR are present in the nerve terminals on the neuromuscular junctions (NMJs) of the levator auris longus muscle of the adult mouse. Exogenously added BDNF or NT-4 increased evoked ACh release after 3 h. This presynaptic effect (the size of the spontaneous potentials is not affected) is specific because it is not produced by neurotrophin-3 (NT-3) and is prevented by prein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(78 citation statements)
references
References 44 publications
2
76
0
Order By: Relevance
“…BDNF interaction with tropomyosin-related kinase B receptors and presynaptic muscarinic receptors modulates transmitter release in adult rodent motor nerve terminal, which can improve stroke motor function recovery [51]. Previous studies reported that catalpol increased the hippocampal neuroplasticity in the aged rats [52] and attenuated MPTP-induced neuronal degeneration of nigral-striatal dopaminergic pathway in mice [53] partly attributed to BDNF upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…BDNF interaction with tropomyosin-related kinase B receptors and presynaptic muscarinic receptors modulates transmitter release in adult rodent motor nerve terminal, which can improve stroke motor function recovery [51]. Previous studies reported that catalpol increased the hippocampal neuroplasticity in the aged rats [52] and attenuated MPTP-induced neuronal degeneration of nigral-striatal dopaminergic pathway in mice [53] partly attributed to BDNF upregulation.…”
Section: Discussionmentioning
confidence: 99%
“…No differences were found between the muscles injected with PBS and those that were not, which suggests that the injection procedure did not in itself induce changes in the overall morphology of the motor end plate and nerve terminals. The solutions were administered at a concentration in accordance with the previously reported biological action of the substance [15,22,23] . The final concentration of dimethyl sulfoxide (DMSO) in control and drugtreated preparations was 0.1% (v/v).…”
Section: Injection Proceduresmentioning
confidence: 99%
“…The influx of external Ca 2+ required for Ca 2+ -triggered exocytosis and the fast mode of endocytosis seems to be promoted with the involvement of the presynaptic mAChR [34] , and interaction with the AR [44] but also with the BDNF-TrkB receptor pathway [23,43] . The mAChR and AR pathways (M 1 and A 1 receptors) share a link mediated by the set phospholipase C-phosphatidylinositol 4,5-bisphosphate (PIP2)-diacylglycerol (DAG)-PKC, which modulates P/Q-type voltage-dependent calcium channels [34,43] .…”
Section: Relation Between Machrs and Arsmentioning
confidence: 99%
“…We further provided evidence that p75NTR is important for BDNF-induced postsynaptic Ca 2+ elevation and synaptic potentiation at the developing NMJ. A recent study demonstrated that inhibition of either the TrkB receptor or p75NTR could inhibit synaptic potentiation at the rodent NMJ, although it was not determined whether the receptors were required pre- or postsynaptically (Garcia et al, 2010). In addition, a postsynaptic role of p75NTR has been implicated in regulation of dendritic spine density and dendritic complexity (Zagrebelsky et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been well documented that blockade of TrkB function restricts BDNF-induced potentiation at the NMJ and at CNS synapses (Lohof et al, 1993; Kang and Schuman, 1995). Recently, p75NTR has been shown to be present at both presynaptic and postsynaptic sites in the adult mouse NMJ (Garcia et al, 2010). However, a functional role of p75NTR in neurotrophin-induced synaptic enhancement at NMJ has not been clearly established.…”
Section: Introductionmentioning
confidence: 99%